Enhancing ITNY students' comprehension of philanthropy through project-based learning - Muh. Iqbal; Lukis Alam; Cahyo Ibrahim Gumilang (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2024)
This study explores the effectiveness of Project-Based Learning (PBL) as a pedagogical approach to enhancing students' understanding of philanthropy at the Institute of Technology National Yogyakarta (ITNY). The research aims to assess how PBL can deepen students' knowledge and practical engagement with philanthropic activities, fostering a more profound appreciation and awareness of social responsibility. Through the integration of real-world projects, students were given opportunities to collaborate, plan, and execute philanthropic initiatives, allowing them to experience firsthand the impact of their contributions.Society 5.0 comes with an orientation to address various social issues, including economic challenges. With the increasing number of students, there is a significant opportunity to respond to Society 5.0 by enhancing students' understanding of philanthropy. Therefore, the aim of this research is to demonstrate that a project-based learning approach is an effective method for deepening students' understanding of philanthropy at ITNY. The methodology involves case studies with data collection through interviews, observations, and documentation, while supporting data is gathered from literature. The results indicate that the term philanthropy is not yet familiar among ITNY students; conversely, they are more acquainted with zakat, infaq, sedekah, and wakaf (ZISWAF), as these have become part of their behavioral beliefs. Through project-based learning implemented in Islamic education courses, students not only become familiar with philanthropy but also gain a deeper understanding. Ultimately, students are able to synergize their technical skills with their beliefs in engaging in philanthropy, as evidenced by the products they create.